Vascular Complications in Coxiella burnetii Infection: A Report of Two Cases - Victoria A.L. Kanowski; Sherab G. Bhutia (EJVES Vascular Forum, 2023)
Introduction: First described in 1937, Q fever remains a relatively new disease, with much to be learned about its presentation and diagnosis. Due to its role in the development of aortic aneurysms and vascular graft infections, its implications in the vascular domain have become increasingly reported. This is a report of two cases of vascular complications associated with Coxiella burnetii infection, and the challenges in managing their unique presentations. Reports: Case 1: A 70 year old man with a prosthetic aortobiiliac graft and past Q fever infection presented with acute sepsis. Abdominal computed tomography (CT) showed soft tissue thickening and stranding around the graft, and locules of gas within the vessel. Pelvic magnetic resonance imaging (MRI) revealed a chain of abscesses within the right gluteal region, of which aspirate grew Prevotella oris and Escherichia coli. Open explanation of the aortic graft and replacement by superficial femoral vein was performed. Tissue culture confirmed a polymicrobial infection, and PCR of the aortic wall and pre-aortic lymph node was positive for Q fever. He was treated for recrudescent Q fever infection with a good outcome and recovery. Case 2: A 73 year old man had an incidental abdominal aortic aneurysm (AAA) identified at the time of Q fever diagnosis. Following an incomplete course of doxycycline and hydroxychloroquine, the aneurysm rapidly progressed, leading to presentation with right flank pain. Fluorodeoxyglucose (FDG) positron emission tomography (PET) showed multiple foci of uptake within the aneurysm wall. Open AAA repair with a polyester graft was performed, with AAA tissue positive for Q fever on PCR. The operation was successful, with the patient continuing clearance therapy at time of writing. Discussion: Q fever infection poses serious implications for patients with vascular grafts and AAAs, and thus, should be considered in the differential diagnosis of mycotic aortic aneurysms and in aortic graft infections.